Bibliographic and Documentary Heritage of the Universidad Pedagógica y Tecnológica de Colombia: Teacher training Schools Collection. Information course 1932 - Pardo Espejo , Nelly Estella; Rodríguez Ochoa, Dilsa Yamile; Márquez Barrera, Luz Eliana; Flórez Valencia , Dina Vanessa; Orrego Montoya, Clara Mónica (Revista General de Información y Documentación, 2023)
The article describes the state of the Bibliographic and Documentary Heritage of the Universidad Pedagógica y Tecnológica de Colombia UPTC, specifically the documents related to the teacher training schools collection and the information course 1932. These documents give an account of the educational processes, orientations and transformations education in Colombia during the 1930s. The study presents a qualitative approach with a systematic design grounded theory. Therefore, the documentary analysis technique was used. A documentary analysis matrix and an ad hoc semi-structured in-depth interview were applied to university officials who met the inclusion criteria, such as being numeraries of the Jorge Palacios Preciado Library and Patrimonial Archive of the university, being in charge of the collections and archives for more than 15 years; and interviews with academics and researchers, teachers who are characterized by having carried out research projects and works making direct use of heritage collections. The results show that the UPTC Bibliographic and Documentary Heritage of teacher training schools collection has a historical, symbolic and educational value. As an educational reference, its value is significan, since it marks the identity and pedagogical character of the institution and of Colombia, allowing to know the teaching practices, learning theories, pedagogical currents, positions regarding beliefs and culture in the country.
Keywords: Heritage; Education; Identity; Memory; Collection; Teacher training schools